(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Elevated high-density lipoprotein cholesterol (HDL-C) levels have been shown to be protective against cardiovascular disease. However, the association of specific lipoprotein classes and ischemic stroke has not been well defined. Objectives:To evaluate the association between HDL-C and ischemic stroke in men and women, and to compare the results with a control sample of the same age group. Methods:A hospital based case-control study was done comparing serum HDL-C levels in 48 ischemic stroke patients to 50 controls recruited from Al-Imamain Al-Kadhemain Medical City, all patients and control had negative past medical history, negative history for smoking and alcohol. Serum lipid profile was determined in all of them. Results :This study showed that regarding the serum HDL-C levels, 41 (85.4%) patients were found to have low levels (less than 40 mg/dl) while among the control group, only 19 (38%) have shown low serum HDL-C level. Conclusion:The study showed that there is a significant association between the low level of serum HDL-C cholesterol and the risk of ischemic stroke in this population. Keywords: cholesterol, lipoproteins, HDL-cholesterol, ischemic stroke